Microwave Differential Circuit Design Using Mixed Mode S-Parameters. - Eisenstadt, William (Artech House microwave library., 2006)
Gain hands-on understanding of powerful new mixed-mode scattering parameter techniques and their applications in microwave circuit design, straight from the inventors of the techniques themselves. This groundbreaking resource uses the original research and application work in the field to describe mixed-mode S-parameter principles. Supported with over 150 illustrations, the book thoroughly explains practical techniques that help you more effectively analyze differential and multi-port systems; measure and describe multi-port circuit performance; and conduct differential circuit analyses for is.